Innovative strategies for photodynamic therapy against hypoxic tumor - Xiaotong Li; Lei Chen; Miaoting Huang; Shaoting Zeng; Jiayi Zheng; Shuyi Peng; Yuqing Wang; Hong Cheng; Shiying Li (Elsevier, 2023)
Photodynamic therapy (PDT) is applied as a robust therapeutic option for tumor, which exhibits some advantages of unique selectivity and irreversible damage to tumor cells. Among which, photosensitizer (PS), appropriate laser irradiation and oxygen (O2) are three essential components for PDT, but the hypoxic tumor microenvironment (TME) restricts the O2 supply in tumor tissues. Even worse, tumor metastasis and drug resistance frequently happen under hypoxic condition, which further deteriorate the antitumor effect of PDT. To enhance the PDT efficiency, critical attention has been received by relieving tumor hypoxia, and innovative strategies on this topic continue to emerge. Traditionally, the O2 supplement strategy is considered as a direct and effective strategy to relieve TME, whereas it is confronted with great challenges for continuous O2 supply. Recently, O2-independent PDT provides a brand new strategy to enhance the antitumor efficiency, which can avoid the influence of TME. In addition, PDT can synergize with other antitumor strategies, such as chemotherapy, immunotherapy, photothermal therapy (PTT) and starvation therapy, to remedy the inadequate PDT effect under hypoxia conditions. In this paper, we summarized the latest progresses in the development of innovative strategies to improve PDT efficacy against hypoxic tumor, which were classified into O2-dependent PDT, O2-independent PDT and synergistic therapy. Furthermore, the advantages and deficiencies of various strategies were also discussed to envisage the prospects and challenges in future study.